Weight width carapace relationship in the crab hepatus-pudibundus (herbst, 1785) (crustacea, decapoda, calappidae) of the Ubatuba region, SP, Brazil - Mantelatto, FLM; Fransozo, A. (Inst Tecnologia Parana, 1992)
In populational studies, the weight/width carapace relationship analysis, can furnish indications about the individual physiological variations as a function of the environment, and it can indicate sexual dimorphism. The goal of this research is to find the mathematical expressions of weight/width carapace relationship in the crab Hepatus pudibundus. This study was accomplished by analysing the crabs that were sampled monthly with a shrimp fishing boat equipped with 2 otter-trawl nets, during the period from november/1988 to october/1989. A total of 624 specimens were obtained composed of 244 males and 380 females. In each group the sex, the weight (PE) and the carapace width (LC) were determined. The obtained values agree with the studied range, showing variations during male and female development, represented by the potential function of the equation Y = aX(b). Such variations are probably related to reproductive strategies.
Keywords: HEPATUS-PUDIBUNDUS; WEIGHT WIDTH; CRUSTACEA; BRACHYURA